(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Vanijajiva O, Pornpongrungrueng P. 2020. Inter-primer binding site (iPBS) markers reveal the population genetic diversity and structure of tropical climbing Cissampelopsis (Asteraceae) in Thailand. Biodiversitas 21: 3919-3928. Cissampelopsis is a small climbing tropical Asian genus of Asteraceae-Senecioneae. In Thailand, the genus is represented by two species, C. corifolia and C. Volubilis, distributed through the mountain evergreen forest. Study on the genetic diversity and structure of populations of both Cissampelopsis species provide better understanding of the biology and pattern of species diversification in the genus. To identify the genetic diversity, we used the inter-primer binding site (iPBS) retrotransposon system, in 96 accessions of Cissampelopsis species collected from different regions in Thailand. A total of 120 iPBS bands were scored as presence? absence characters. Results from UPGMA and PCoA analyses indicated that C. corifolia and C. volubilis are different species. Genetic diversity and genetic differentiation among and within populations of C. volubilis is higher than C. corifolia. Molecular Variance (AMOVA) analysis of both species indicated that the genetic variance value within populations is higher than among populations of each species. Bayesian model-based STRUCTURE analysis detected two gene pools for both Cissampelopsis and showed admixture within individuals. Differences among the two Cissampelopsis species, in total diversities and levels of population differentiation, indicated that the genetic structure of Cissampelopsis populations are congruent with long-lived perennial habit with regional distribution, even for congeneric species, may vary considerably. This study suggests the effectiveness of the iPBS marker system to estimate the population genetic diversity and structure of Cissampelopsis genotypes.